New Arabian nights - Stevenson, Robert Louis, 1850-1894 (Floating Press, 2009)
Considered by many to contain pioneering works of English writing, Robert Louis Stevenson's New Arabian Nights collects together his short stories that were originally published in periodicals between 1877 and 1880. Holding some of Stevenson's first works of fiction to be published, some of these stories are thought by critics to be his best.